Exploring the mechanisms behind swimming performance limits to ocean warming and acidification in the Atlantic king scallop, Pecten maximus - Bock, Christian; Götze, Sandra; Pörtner, Hans O.; Lannig, Gisela (Frontiers in Ecology and Evolution, 2024)
Recently, we could show that scallops show limitations of muscular performance like a reduced force under ocean warming and acidification. However, the underlying mechanisms at the cellular level are not completely understood. Metabolomics has become a valuable tool to evaluate the responses of marine organisms to various stressors. In the present study we therefore used a semi-targeted, multi tissue NMR based metabolomic approach to analyze metabolite patterns in the Atlantic king scallop, Pecten maximus, that were long-term acclimated to different end of century conditions of ocean warming (OW), ocean acidification (OA) and their combination (OWA). We investigated tissue specific metabolic profiles and metabolite concentrations in frozen tissues from gills, mantle and phasic and tonic adductor muscle of P. maximus under present conditions using 1 H-HR-MAS NMR spectroscopy. A set of 33 metabolites revealed a clear tissue-specific pattern which can be attributed to the individual functions of the respective tissue type. We then evaluated the impact of OW, OA and OWA on the metabolic profiles of the different tissues. OW was the main driver of the changes in metabolites. In particular, energy-related metabolites seem to play an important role in the physiological response of scallops to OW and OWA. In combination with pathway analysis and network exploration we propose the mechanisms and physiological requirements behind these metabolic changes and a possible correlation between metabolic changes in the adductor muscle and limited swimming performance of P. maximus under future climate. While the metabolic response of the phasic muscle seems to mainly depend on net consumption of energy related metabolites such as ATP and phospho-L-arginine, the tonic muscle seems to rely on metabolizing specific amino acids and beta-oxidation to account for the elevated energetic requirements under ocean warming and acidification.